THE VERBAL WORLD PICTURE AND ITS REPRESENTATION IN ENGLISH PHRASEOLOGY - Kushnierova , Anna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article deals with the verbal world picture analysis through the prism of English phraseology and the peculiarities of phraseologization of phrases in view of the culturally motivated vision of the world by particular linguistic communities. The objective of this paper is a study of phraseological (set) expressions in order to identify ontological and cultural components in language. The certain tendency of illustrating verbal world picture in phraseological (set) expressions was revealed. The study has demonstrated that phraseological (set) expressions, which most vividly illustrate the British cultural identity, are genetically linked to the most common and widespread areas of human activity, namely food, the natural world that surrounds us, and certain "endemic" phenomena of British life. The phraseological picture of the world acts as a set of knowledge about the world and can give a complete description of a particular nation or people. The examples of phraseological set expressions given allow us to see the phraseological composition of language reflects cultural identity not only as a fragment of reality, given to the ethnic community in immediate perception, but also the lifestyle, beliefs, worldviews, national character, temperament, value system - the mentality of the people, their social consciousness in general. Thus, the phraseology becomes a certain extra-linguistic reality that not only realizes the linguistic consciousness and perception of the speaker, but also forms a vision through the prism of phraseology, which is based on the cultural territorial perception of a nation._____________References• Apresyan, D. «The emotional system. The image of a person according to the language: an attempt to describe the system.» Questions of linguistics 1 (1995): 37–65.• Barantsev, T. English-Ukrainian phraseological dictionary: Near 30000 phraseological phraseological phrases (Kiev, Publishing house “Radyanska school”, 1969), 1052.• Brutyan, A. «Language and picture of the world.» Scientific. doc. higher school Philosopher. Sciences 1 (1973): 108–111.• Weisgerber, L. Native language and the formation of the spirit (Moscow, Book House "LIBRICOM", 2009), 232.• Humboldt,  Selected works on linguistics (Moscow, 1984), 231.• Kornilov, O. A. Language pictures of the world as derivatives of national mentalities (Moscow, CheRo, 2003), 349.• Kunin, A. V. English-Russian phraseological dictionary (Moscow, Russian language, 1984), 944.• Levchenko, O. P. «Phraseological representation of the world.» Modern and conceptual images of the world, Vol. scien.works7 (Kyiv, KNU, 2002): 307–315.• Nimetsko-Ukrainian phraseological dictionary. 2 volumes, B. I. Gavris, O. P. Prorochenko (Glad. school., 1981), T. 1, 416; T. 2, 382.• Potebnya, A. A. «Language and nationality.» Aesthetics and poetics (Moscow, Art, 1976): 253–285.• Radchenko, O. A. Language as a world-creation. Linguophilosophical concept of neo-Humboldtianism, T. 1 (Moscow, 1999).• Selivanova, O. Suchasna linguistics: terminology encyclopedia (Poltava, Dovkіlya – K, 2006), 716.• Sepir, E. Selected works on linguistics and cultural studies (Moscow, Progress, 1993), 656.• Telia, V. N. The connotative aspect of the semantics of nominative units (Moscow, 1986): 143.• Telia, V. N. «Metaphorization and its role in creating a linguistic picture of the world.» The role of the human factor in language: Language and picture of the world (Moscow, Nauka, 1988): 173–204.• Telia, V. N. Russian phraseology. Semantic, pragmatic and linguoculturological aspects (Moscow, School "Languages of Russian Culture", 1996), 288.• Uzhchenko, V. D., Uzhchenko, D. V. Phraseology of modern Ukrainian language. Pidruchnik (Kyiv, Znannya, 2007), 494.